Treatment of landfill leachate by anaerobic digestion, biogas yield and co-digestion possibilities - Polley, Devnita; Jain , Sudhir (Journal of Postharvest Technology, 2022)
One of the significant concerns related to rapid urbanization in developing countries is solid waste management. In a developing country like India, municipal authorities are struggling to deal with solid waste management. Leachate, byproduct of landfill disposal is adding to its concern, by polluting ground water, surface water and adjacent soil quality. This study deals with the anaerobic treatment potential of landfill leachate. As anaerobic digestion treats the leachate as well as generates bio gas which has economical value. But due to its complex nature and heterogeneous properties biogas production is often not constant. Co-digestion with suitable material can provide a consistent source and undisturbed digestion. Various co digestion potentials are described in this paper.